Northern fur seals data - Jeanniard-Du-Dot, Tiphaine (Dryad Digital Repository, 2016)
Data was collected on northern fur seal females during the breeding season on St Paul island, Bering Sea, Alaska from a daily Diary tag from Wildlife Computers. Column headings include "Date", "Time","Depth", "External Temperature", "int mX", "int mY", "int mZ", "int aX", "int aY", "int aZ", "Light Level", "Velocity", "Wet/Dry", "Wet/Dry", "Hour", "Battery Voltage", "Protocol". int mX, Y, Z refer to magnetic field recorded on the 3 body axes, and int aX, Y, Z to the acceleration recorded on the same axes.